DESIGN AND DEVELOPMENT OF A LEAKAGE CURRENT AND POWER MONITORING SYSTEM WITH NODEMCU ESP 8266 FOR HOUSEHOLD ELECTRICITY - Agung Nugroho; Randi Adzin Murdiantoro; Nasrulloh Adzin Murdiantoro (Program Studi Teknik Elektro Universitas Peradaban, 2023)
The research objective is to create a tool for monitoring household electrical equipment whether there is leakage current and excess power through the NodeMCU microcontroller. Through this tool displays the electric current, voltage and power of household electrical equipment displayed on the LCD and Blynk. Research and Development (R&D) is the methodology used, which consists of five steps, namely problem analysis, data collection, system design, system implementation and testing. Data collection is in the form of electric power values using the radio, the data is displayed on the LCD and blynk. The measurement displays a current value of 0.03 A, a voltage value of 226.70 V, a power value of 3.80 Watts. The second test is using electric power using a TV, the data is displayed on the LCD and blynk. The third measurement is a current of 0.50 A, a voltage of 227.10 V, a power of 74.20 W. The fourth measurement is a comparison of the voltage value on the device with the PLN voltage with a multimeter measurement and the comparison produces the same value. The fifth measurement is to measure the value of the leakage current on the radio, this measurement produces a current value of 0.09. There is a difference in the current value if it experiences a leakage current, if there is a leakage current then the current value will be greater than in normal conditions but if it is under normal current conditions then the current value is small.